2018
DOI: 10.7819/rbgn.v20i2.3049
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Barriers in Single Stock Prices: Evidence from Three Emerging Markets

Abstract: Purpose -The purpose of the study is to examine the prices of some of the most widely traded stocks from Taiwan, Brazil and South Africa for indications of psychological barriers at round numbers.Design/methodology/approach -The sample under study includes a group of 24 stocks (8 for each one the emerging markets) during the period 2000-2014. We test for uniformity in the trailing digits of the stock prices and use regression and GARCH analysis to assess the differential impact of being above or below a possib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…The Taiwanese index and the Indonesian index exhibited some signs of psychological barriers. Lobão and Fernandes (2018) found no consistent psychological barriers in individual stock prices near round numbers in the markets of Taiwan, Brazil and South Africa in the period 2000-2014. The authors also documented that the relationship between risk and return tended to be weaker in the proximity of round numbers for about half of the stocks under study.…”
Section: Previous Empirical Studiesmentioning
confidence: 84%
See 1 more Smart Citation
“…The Taiwanese index and the Indonesian index exhibited some signs of psychological barriers. Lobão and Fernandes (2018) found no consistent psychological barriers in individual stock prices near round numbers in the markets of Taiwan, Brazil and South Africa in the period 2000-2014. The authors also documented that the relationship between risk and return tended to be weaker in the proximity of round numbers for about half of the stocks under study.…”
Section: Previous Empirical Studiesmentioning
confidence: 84%
“…Shawn and Kalaichelvan (2012) examined five indices (ATX, CAC, DAX, FTSE, SMI) in the period 2001-2011, having found evidence for barriers in only one index (SMI) at the 1,000-level but no significant evidence of barriers at the 100 and 1,000 levels in the other indices. Bahng (2003) and Lobão and Fernandes (2018) carried out two of the few studies regarding the existence of psychological barriers in emerging stock markets. Bahng (2003) conducted the first study about the topic on Asian stock markets, using the daily prices of seven indices (South Korea, Taiwan, Hong Kong, Thailand, Malaysia, Singapore and Indonesia) from the beginning of 1990 to the end of 1999.…”
Section: Previous Empirical Studiesmentioning
confidence: 99%
“…The absence of psychological barriers is consistent with a highly informationally efficient market. With their presence detected, with a market dominated by noise traders (Lobão and Fernandes, 2017), where prices may be dictated by complex patterns of shifting fads and moods. It is not possible to make comparisons with the results of other authors, as this analysis applies to a specific market that has not been studied in the literature.…”
Section: Rbf 135mentioning
confidence: 99%
“…More recently, Berk et al (2017) and Lobão and Fernandes (2018) conducted studies on individual stock prices and found conflicting results. Berk et al (2017) examined the prices of 77 individual stocks belonging to 15 frontier equity markets, i.e., markets that are not developed enough to be considered as "emerging".…”
Section: Previous Findingsmentioning
confidence: 99%